KAJIAN KARBON PADA PENGEMBANGAN PRODUK UNGGULAN BUAH-BUAHAN RAMAH LINGKUNGAN DI KABUPATEN TUBAN JAWA TIMUR - Kristiawan, Kristiawan; Maimunah, Maimunah (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
The determination of national and regional leading commodities is the first step towards agricultural development that is based on the concept of efficiency to achieve comparative and competitive advantage in the face of trade globalization. Commodity development that has a comparative advantage in terms of supply is characterized by its superiority in its growth in the biophysical, technological, and socio-economic conditions of farmers in a region. This is important because changes in the external environment through the process of globalization require local governments (provincial / district / city) to increase their competitiveness, so they are able to compete globally. The agricultural commodities in the GRDP structure contribute significantly to the economy in Tuban Regency. The purpose of this study is to describe the typolology of the leading producer of environmentally friendly fruit commodities based on land suitability, determine environmentally friendly superior commodities for fruits in Tuban Regency, analyzing the optimization of the farm management of the development of superior commodities of environmentally friendly fruits in Tuban. Quantitative analysis used in this study is the analysis of regional economic structures using the Location Quotient (LQ) approach, which is the approach used to determine the commodity in an area includes a base or non basis based on harvested area or quantity of production each year. While environmental aspects are approached through the calculation of biomass and carbon content and CO2 uptake of friendly superior fruit crops environment. The results of the study based on the Location Quotient (LQ) method show that the potential of star fruit, red guava and mango commodities in Tuban is classified as base, while citrus fruit is classified as non-base. Socially viable farming based on employment is star fruit farming and economically viable based on income is mango fruit farming and environmentally viable based on carbon biomass is mango fruit farming. Whereas socially, economically and environmentally viable farming is mango fruit. Based on the calculation of carbon biomass, the largest carbon biomass is obtained from mango fruit plants in the amount of 61,823.20 kg / ha. This is because the mango fruit plant has a larger stem than other commodity crops such as star fruit, red guava or orange. In addition, mango commodity plants have a relatively long age so that it has a relatively large carbon biomass. Besides being influenced by plants themselves, carbon biomass that is formed can also be influenced by quality in land management.